Niektoré makroekonomické aspekty ekonomického rastu - Hontyová, Kajetana; Lisý, Ján (Univerzita Pardubice, 1999)
All economics problems are related with efficiency and economic growth. Economy without growth is regarded as economy in stagnation with features like rising of unemployment and social tension, and citizens that are still less satisfied with the distribution of declining resources. Sources of wealth of a nation and of economic growth are: labour, capital, rate of savings and investments, level of application of research and technology, human capital, free market economy , standard of institutionalized order of a society, freedom of property and enterprise, accepting of legal, moral and ethical principles, open economy and effective implementation of economy policy. At present, a model of steady economics growth is favoured, that should satisfy the needs of today's civilisation, but also the needs of future generations. Furthermore it should stabilize the population and eliminate the negative externalities of economic growth. Analysis on efficiency of economy and economic growth with help of GDP means considerable inaccuracies and imperfection. Therefore, recently economists started taking into consideration a new macroeconomic indicator - genuine progress indicator GPI, which enhances the accuracy of measures of efficiency economy.
Keywords: makroekonomie; ekonomický růst; negativní účinky; důsledky